National Household Education Survey, 2001 ([Verlag nicht ermittelbar], 2003)
The National Household Education Survey (NHES) reports on the condition of education in the United States by collecting data at the household level rather than using a traditional, school-based data collection system. The surveys attempt to address many current issues in education, such as preprimary education, school safety and discipline, adult education, and activities related to citizenship. This survey included three topical survey components. The Early Childhood Program Participation (ECPP) Survey (Part 1) gathered information on the nonparental care arrangements and educational programs of preschool children, such as care by relatives, care by persons to whom they were not related, and participation in day care centers and preschool programs including Head Start. The Before- and After-School Programs and Activities (ASPA) Survey (Part 2) addressed relative and nonrelative care for school-age children during the out-of-school hours, including home schooling as well as participation in before- and/or after-school programs, activities, and self-care. The Adult Education and Lifelong Learning (AELL) Survey (Part 3) collected data such as type of program, employer support, and credential sought for participation in the following types of adult educational activities: English as a second language, adult basic education, credential programs, apprenticeships, work-related courses, and personal interest courses. Some information on work-related informal learning activities was gathered as well.